PENERAPAN KEGIATAN MENGGAMBAR UNTUK MENGEMBANGKAN MOTORIK ANAK DI RA ASSYIFA MEDAN JOHOR - Jamilah Jamilah (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This research was conducted at RA Assyifa Medan Johor with the title application of drawing activities to develop early childhood motor skills at RA Assyifa. This research study to study how the drawing process develops motor aspects of early childhood in RA Assyifa Medan. The benefit of this research is to find out whether drawing activities can really develop children's motor skills. The technique or method in this study uses qualitative research types with research instruments consisting of observation, documentation and interviews. The results of this study are by drawing using a pencil so the child is included in the criteria both in motor development because it is in accordance with the development of the child's age.